199 Lower aortic valve calcium scores by computed tomography scan. A potential new red flag of concomitant cardiac amyloidosis in patients with severe aortic stenosis. (8th December 2021) - Ponziani, Alberto; Saturi, Giulia; Santona, Laura; Sguazzotti, Maurizio; Caponetti, Angelo Giuseppe; Massa, Paolo; Gagliardi, Christian; Giovannetti, Alessandro; Lovato, Luigi; Attinà, Domenico; Bonfiglioli, Rachele; Saia, Francesco; et al.
Abstract: Aims: Cardiac amyloidosis (CA) and degenerative aortic stenosis (AS) are two diseases often combined but the diagnosis of both these conditions is challenging because these two illnesses share common echocardiographic characteristics. Different predictors have been proposed in the last few years, including clinical, ECG-graphic, and echocardiographic features. To identify a new marker of concomitant CA in patients with severe AS using computed tomography scan (CT). Methods and results: Fifty-five patients with severe AS and suspicion of concomitant CA were retrospectively enrolled. Patients with a bicuspid aortic valve, previous aortic valve replacement, or an incomplete diagnostic workup for CA were excluded. Thirty-three patients underwent CT-scan and were included in the final analysis. None of the patients had at laboratory tests suspicion for AL amyloidosis; 12 patients (AS-CA) had positive 99 m Tc-DPD bone scintigraphy (two with visual score 1, eight score 2 and two score 3), 21 patients (AS-alone) had negative bone scintigraphy (visual score 0). AS-CA patients had a median age of 85.5 years (vs. 82) with only one female patient (vs. 8 in the AS-alone group). AVA indexed were almost comparable between AS-CA and AS-alone groups (0.4 vs. 0.3 mm 2 /m 2, P = 0.25). Stroke volume evaluated by pulsed Doppler, maximum and mean gradient were significatively lower in AS-CA group (respectively 30 vs. 41 ml/m 2, P = 0.017, 62 vs. 74 mmHg, 0.038 and 33 vs. 46 mmHg, P = 0.022) with a higher percentage of paradoxical low flow-low gradient aortic stenosis in AS-CA group (7 patients, 58% vs. 3 patients in AS-alone 14%, P = 0.027), in line with the literature. ECG at first presentation in AS-CA group showed atrial fibrillation in eight patients (67%), vs. two patients in the AS-alone group (10%), and lower QRS voltages (peripheral QRS score 40 mV vs. 51 mV, P -value = 0.017; total QRS score 113 mV vs. 155 mV, P -value = 0.005). The echocardiogram showed a more thickened IVS and PW in AS-CA patients (17 vs. 15 mm, P = 0.05 and 15 vs. 14 mm, P = 0.013), an increased left ventricular mass (441 vs. 356 g, P = 0.036) with a reduction of longitudinal systolic function (septal S wave at TDI 4.4 vs. 5.2 cm/s, P = 0.026, lateral S wave 4.1 vs. 5.6 cm/s, P = 0.024) and a lower myocardial contraction fraction (12% vs. 14%, P = 0.036). CT-aortic valve calcium was valued and quantified by an experienced operator. A statistically significant difference between AS-CA and AS-alone groups was observed in calcium score (3345 vs. 4785 Hounsfield units, P = 0.037) calcium volume (2411 vs. 3626 mm 2, P = 0.03) and calcium mass (687 vs. 1147 g, P = 0.023). Conclusions: This study is the first to our knowledge to use relative aortic valve calcium score evaluation from CT imaging to define patients with severe AS with or without concomitant CA in addition to the classical clinical, ECG graphic, and echocardiographic features. CT-aortic valve calcium burner was significatively lower in patients with concomitant CA.